2004
DOI: 10.1074/jbc.m310290200
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Rates of Transcript Elongation by Single RNA Polymerase Molecules

Abstract: Single-molecule measurements of the activities of a variety of enzymes show that rates of catalysis may vary markedly between different molecules in putatively homogenous enzyme preparations. We measured the rate at which purified Escherichia coli RNA polymerase moves along a ϳ2650-bp DNA during transcript elongation in vitro at 0.5 mM nucleoside triphosphates. Individual molecules of a specifically biotinated RNA polymerase derivative were tagged with 199-nm diameter avidin-coated polystyrene beads; enzyme mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
102
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 69 publications
18
102
1
Order By: Relevance
“…There are some similarities between template-dictated polymerizations driven by ribosome and RNAP. The run time distribution of RNAP has been measured and found to be Gaussian [59]. This is consistent with the Gaussian run time distribution for ribosomes predicted in this paper which follows from very general arguments based on the central limit theorem.…”
Section: Discussionsupporting
confidence: 88%
“…There are some similarities between template-dictated polymerizations driven by ribosome and RNAP. The run time distribution of RNAP has been measured and found to be Gaussian [59]. This is consistent with the Gaussian run time distribution for ribosomes predicted in this paper which follows from very general arguments based on the central limit theorem.…”
Section: Discussionsupporting
confidence: 88%
“…Single-molecule experiments have shown that RNAP advances by one base at a time along DNA, with translocation tightly coupled to RNA synthesis, and that it likely operates by a Brownian ratchet-type mechanism (7-9). Single-molecule experiments have identified and characterized long-lived heterogeneities in RNAP conformations (24), elongation rates (12,13,101), and pause propensities (10). Other single-molecule studies have found that transcriptional initiation involves scrunching of the DNA template until contacts with the promoter are released (5,6), and supplied evidence for an elongation-incompetent intermediate state preceding transcriptional termination (14).…”
Section: Resultsmentioning
confidence: 99%
“…One early single-molecule study, which was conducted at comparatively low spatial and temporal resolution, reported that wild-type RNAP can spontaneously switch velocity states (100). However, subsequent studies have failed to confirm any such switching (12,13,101), casting doubt on the finding. To date, only one other observation of velocity-state switching has been reported, in this case for an RNAP mutant bearing a point mutation in the β-subunit (but not for the wild type) (13).…”
Section: On-pathway Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, RNA polymerase can pause for a longer time and then backtrack (33), which is a behavior that may be part of the proofreading mechanism of the enzyme (34). Last, the diversity in transcription rates (Ն5-fold) of single molecules far exceeds that expected for a single transcribing species (35). Because each molecule maintains its rate for the duration of the measurements (Ϸ5 min), this variation is not due to rapidly interconverting conformers.…”
mentioning
confidence: 99%